Pentingnya self – awareness dalam pendidikan anak usia dini - Ningsih, Rizka Septia (Maliki Interdisciplinary Journal, 2026)
Self-awareness is a crucial element in the social–emotional development of young children. This aspect includes the child’s ability to understand themselves, both internally—such as emotions, moods, and perceptions—and externally, namely how they present and behave within their social environment. From a humanistic perspective introduced by scholars like Carl Rogers and Arthur Combs, learning becomes meaningful when it centers on the learner and aims to help them recognize their potential, unique characteristics, and personal capacities. During early childhood, self-awareness develops gradually through direct experiences, social interactions, the ability to recognize oneself in a mirror, and increasingly advanced language skills. The use of visual media such as videos can also enhance children’s ability to understand their emotions and their roles in social interactions. Children aged 4–5 begin to identify their strengths and weaknesses, regulate their emotions, and show independence and self-confidence. Strengthening this aspect is essential as it serves as the foundation for prosocial behavior and other social–emotional competencies. Therefore, early childhood education plays a significant role in providing appropriate stimulation so that children can grow into stable, wise individuals who are capable of interacting positively with their surroundings.